PERAN GURU TAHFIDZ DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR’AN PESERTA DIDIK DI SEKOLAH HUFFADZ QUR’AN TAMAN SARI PERSADA - Bariratun Nadrah; Muhammad Azhar Alwahid; Salati Asmahasanah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study is motivated by the growing demand for quality Qur’an memorization (tahfidz) education, despite the persistent challenges of low memorization retention and student motivation at Sekolah Huffadz Qur’an Taman Sari Persada. The aim of this research is to explore the role of tahfidz teachers in improving the quality of students’ Qur’an memorization. A qualitative approach with a case study design was employed. Data were collected through observation, interviews, and documentation. The findings indicate that tahfidz teachers serve as motivators, guides, innovators, and evaluators. The applied methods include talaqqi, wahdah, kitabah, sima’i, tashih, and muroja’ah, all tailored to the students' individual characteristics. The quality of memorization improved with personal mentoring and consistent instruction. Students expressed positive perceptions of their tahfidz teachers, especially regarding discipline and role-modeling. The study concludes that the effectiveness of tahfidz teachers depends on their ability to adapt teaching strategies and collaborate with parents. Recommendations include enhancing teacher competencies, implementing more flexible halaqah schedules, and providing supportive learning facilities. This study is expected to serve as a reference for educational institutions and future researchers in developing effective and contextual tahfidz strategies in the modern era.